Kualitas Audit: Kajian dari Perspektif Kompetensi, Independensi dan Etika Pada KAP Jojo Sunarjo dan Rekan Cabang Pekanbaru - Kurniawan, Mohd. Ideal; Utami, Rachma (Jurnal Sistem Informasi, Akuntansi dan Manajemen, 2024)
This study aims to determine the importance of the role of competence, independence, ethics on audit quality at KAP Jojo Sunarjo and Partners Pekanbaru Branch. The research method used is a quantitative method with a descriptive approach. The data used in collecting data is a questionnaire. The results show that competence, independence, and ethics play a role in improving audit quality at the Jojo Sunarjo and Partners Public Accounting Firm, Pekanbaru Branch. Competence is the most urgent thing to improve audit quality.